Factors Affecting The Job Performance of Employees at E-Commerce Companies in Indonesia - Mutiara Jannah; Justine Tanuwijaya (Journal of Economics and Business UBS, 2026)
This study aims to analyze the antecedents of job performance by considering the mediating role of work engagement. The variables used in this study are transformational leadership and perceived supervisor support as the independent variables, job performance as the dependent variable, and work engagement as the mediating variable. The respondents of this study consisted of 150 employees at e-commerce companies. Data analysis was conducted using the Structural Equation Modeling (SEM) method with the assistance of AMOS software. The results of this study indicate that transformational leadership has a positive effect on job performance. Transformational leadership has a positive effect on work engagement. Perceived supervisor support has a positive effect on job performance. Perceived supervisor support has a positive effect on work engagement. Work engagement plays a mediating role in the relationship between transformational leadership and job performance, and work engagement also mediates the relationship between perceived supervisor support and job performance. Managerial implications: Management can provide recognition to high-achieving employees in the form of micro-rewards. Small but relevant rewards are often more meaningful than annual awards that are rarely given. In addition, management also needs to provide facilities in the form of professional career development for each individual employee, such as by providing opportunities for training, project rotation, or promotions. This makes employees feel valued because they are recognized as individuals with potential for development.